2007
DOI: 10.1007/s00417-007-0561-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of basal cell carcinoma of the eyelids with 5% topical imiquimod: a 3-year follow-up study

Abstract: Topical imiquimod applied in the form of a 5% cream proved to be a safe, efficacious and sustainable treatment option for nodular BCC of the eyelid in our selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 7 publications
0
21
0
12
Order By: Relevance
“…Uma ação secundá-ria observada foi a indução direta da apoptose das células tumorais pelo imiquimode, que parece ser capaz de ativar a via das caspases (1) . Liberado para uso em CBC superficial e ceratose actínica em 2004 pelo "US Food and Drug Administration " (FDA -U.S.A) (3)(4)(5) e em 2006 pela Agên-cia Nacional de Vigilância Sanitária (Anvisa) ainda permanece em estudo para aplicação no CBC nodular, assim como na área periocular (4,6,7) . O CBC nodular assim como o superficial são subtipos histológicos menos agressivos do CBC (2) e aparentemente mais responsivos a essa medicação.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Uma ação secundá-ria observada foi a indução direta da apoptose das células tumorais pelo imiquimode, que parece ser capaz de ativar a via das caspases (1) . Liberado para uso em CBC superficial e ceratose actínica em 2004 pelo "US Food and Drug Administration " (FDA -U.S.A) (3)(4)(5) e em 2006 pela Agên-cia Nacional de Vigilância Sanitária (Anvisa) ainda permanece em estudo para aplicação no CBC nodular, assim como na área periocular (4,6,7) . O CBC nodular assim como o superficial são subtipos histológicos menos agressivos do CBC (2) e aparentemente mais responsivos a essa medicação.…”
Section: Discussionunclassified
“…A ceratite puntata e a conjuntivite reacional foram os principais efeitos colaterais observados e coincidem com os da literatura (4)(5)(6) . No presente caso uma conjuntivite bacteriana se sobrepôs à conjuntivite reacional, demonstrando a importância do acompanhamento oftalmológico rigoroso no tratamento empregado.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Initial reports of favorable off-label treatment of Bowen's disease of the eyelid [21,22] were followed by case series documenting the successful treatment of both BCC [23][24][25][26][27][28] and later SCC [26]. Carneiro et al reported an 80% clinical and histological cure in 10 patients, whereas Garcia-Martin et al used imiquimod cream 5% 5 days per week for 6 weeks in 15 patients with periocular nodular BCC and had histological remission at 3 months with long-term clinical remission at 24-28 months follow-up in all patients [27,28].…”
Section: Imiquimodmentioning
confidence: 99%
“…It acts by stimulating both innate and cell-mediated immunity pathways, activates antigen-presenting cells through toll-like receptor 7, and stimulates cytotoxic T-cells, Langerhans cells, and natural killer cells to produce interferon-gamma and other cytokines, which cause apoptosis (5). US Food and Drug Administration (FDA) approved IMQ for anogenital warts in 1997, and for superficial basal cell carcinoma (BCC) and AK in 2004 (6,7). Other clinical indications are lentigo maligna, extramammary Paget's disease, Bowen's disease, xeroderma pigmentosum, and molluscum contagiosum (8).…”
Section: Introductionmentioning
confidence: 99%